«Благо посполите» та «користь партикулярна» як мотиви управлінської діяльності старшин України-Гетьманщини 17-18 ст. - Олексій Струкевич (Scientific Papers of the Vinnytsia Mykhailo Kotsyiubynskyi State Pedagogical University Series History, 2026)
The purpose of the article is to examine the moral and political motivations underlying the activities of the Cossack officer elite (starshyna) of the Ukrainian Hetmanate in the seventeenth and eighteenth centuries. It aims to analyze the most significant moral and political dilemma faced by the officer elite, namely the tension between the common good and private interest; to identify the factors that shaped their moral and political motivations; and to determine how the idea of the common good was implemented in contemporary political practice. The research methodology is based on traditional general scientific methods of inquiry as well as specialized methods of historical research. Particular emphasis is placed on a thorough textual analysis of historical sources in order to identify even the most subtle aspects recorded in historical documents. The scientific novelty of the study lies in addressing a new and promising research topic that makes it possible to clarify the role and significance of moral and political factors in the life of the political elite of the Ukrainian Hetmanate. Conclusions. The analyzed material demonstrates that the performance of administrative functions encouraged the Cossack officer elite to justify their activities in terms of the common good, reflecting the evolution of the moral and political culture of the Ukrainian Hetmanate along the lines of the European Enlightenment. The idea of serving the common good was employed by the officer elite to legitimize their claims to public office and to justify their decisions and actions in both domestic and foreign policy. These ideas were manifested in the separation of the Hetman's private treasury from the state treasury, the moral condemnation of clan-based favoritism, the recognition of the need to reconcile the interests of all social estates and groups for the sake of the common good, and the willingness of certain members of the officer elite to subordinate their private interests to the interests of the Fatherland. The predominance of concern for the common good over private interests remained characteristic of the officer elite's political consciousness until the abolition of the Hetmanate.